2007
DOI: 10.1039/b613334g
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial targeting of radioprotectants using peptidyl conjugates

Abstract: Ionizing radiation activates a mitochondrial nitric oxide synthase, leading to inhibition of the respiratory chain, generation of excess superoxide, peroxynitrite production and nitrosative damage. We have measured the radioprotective effects of a nitric oxide synthase antagonist (AMT) versus a free radical scavenger (4-amino-TEMPO) using electrochemical detection of nitric oxide and peroxynitrite. To enhance their efficacy, we have conjugated these compounds to peptides and peptide isosteres-derived from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Although earlier results from our own group have suggested that it is the “perpetual cascade” of cytokines and chemokines that is the critical element in the development of radiation pneumonitis and, ultimately, late radiation fibrosis (Rubin et al 1995, Johnston et al 1996), other investigators have suggested that chronic dysregulation may be due to other mechanisms, such as the maintenance of damage within the mitochondria, leading to an activated inflammatory site as a result of chronic free radical production (Epperly et al 2003, Kanai et al 2007, Zhao & Robbins 2009). Therefore, observation of persistent periods of increased cytokine expression may not be a requirement for confirmation of the presence of ongoing pulmonary damage.…”
Section: Discussionmentioning
confidence: 95%
“…Although earlier results from our own group have suggested that it is the “perpetual cascade” of cytokines and chemokines that is the critical element in the development of radiation pneumonitis and, ultimately, late radiation fibrosis (Rubin et al 1995, Johnston et al 1996), other investigators have suggested that chronic dysregulation may be due to other mechanisms, such as the maintenance of damage within the mitochondria, leading to an activated inflammatory site as a result of chronic free radical production (Epperly et al 2003, Kanai et al 2007, Zhao & Robbins 2009). Therefore, observation of persistent periods of increased cytokine expression may not be a requirement for confirmation of the presence of ongoing pulmonary damage.…”
Section: Discussionmentioning
confidence: 95%
“…Critical amide bonds in these compounds were replaced with (E)-alkene peptide isosteres which improved their bioavailability, possibly due to increased resistance against protease action (4244), and the analogs could be structurally altered to modulate cell membrane passage relative to mitochondrial targeting. ESR spectroscopy and mass spectroscopy confirmed that the gramicidin S–based compounds successfully delivered and concentrated both TEMPO and AMT to mitochondria, whereas the presence of free drugs was not observed (18, 45). Harmful ONO 2 − production in irradiated cells was reduced or eliminated upon treatment with conjugated TEMPO and AMT, respectively (18).…”
Section: Targeting Mitochondriamentioning
confidence: 85%
“…ESR spectroscopy and mass spectroscopy confirmed that the gramicidin S–based compounds successfully delivered and concentrated both TEMPO and AMT to mitochondria, whereas the presence of free drugs was not observed (18, 45). Harmful ONO 2 − production in irradiated cells was reduced or eliminated upon treatment with conjugated TEMPO and AMT, respectively (18). The ability of rats to survive lethal hemorrhagic shock was significantly increased by intravenous injection of the TEMPO-conjugated compound (46).…”
Section: Targeting Mitochondriamentioning
confidence: 85%
See 2 more Smart Citations